Variations in fish community composition and trophic structure under multiple drivers in the Beibu Gulf - Peng, Shuai; Wang, Xuehui; Du, Feiyan; Sun, Dianrong; Wang, Yuezhong; Chen, Pimao; Qiu, Yongsong (Frontiers in Marine Science, 2023)
Beibu Gulf is a semi-enclosed bay with important ecological and economic value of the northwestern South China Sea (SCS). It proved to be a stressed ecosystem and therefore clearly vulnerable to further external disturbances. Data from 26 fishery bottom trawl surveys in the Beibu Gulf from 2006 to 2018 are analyzed to reveal changes in the fish abundance, dominant species composition, diversity, mean trophic level (MTL), and fishing-in-balance index (FiB). Fish abundance decreased significantly (p < 0.05) with increased anthropogenic disturbance (e.g., fishing intensity and land-derived pollutants), with catch rates decreasing from 40.69 kg·h−1 in 2006 to 15.84 kg·h−1 in 2018. Dominant species composition has changed dramatically from 2006 to 2018, with fish communities shifting from demersal to pelagic species, and from large and high-trophic-level species to small and low-trophic-level species. Meanwhile, Margalef’s richness and Shannon–Wiener diversity indexes trend downward. The mean trophic level declines from 3.82 in 2006 to 3.71 in 2018 (at 0.08 trophic level per decade), and decreasing with the decrease of the proportion of high-trophic fish and demersal fish in total catch (p < 0.05). A fishing-in-balance index tends to be < 0, indicating that fish stocks in the Beibu Gulf are overfished; this index declines with decreasing mean trophic level and fish abundance (p < 0.05). Overall, fish stocks in the Beibu Gulf continue to decline and are currently overexploited. Multiple external disturbances, such as fishing (including overfishing, dominance of trawl fishery, and ‘skipper effect’), habitat disturbance, pollution, and temperature changes, may have contributed to significant changes in fish communities and trophic structure in the Beibu Gulf.